Β-Galactosidase-dependent metabolic glycoengineering of tumor cells for imaging and immunotherapy. Issue 15 (2nd February 2022) - Li, Yanchun; Gong, Liang; Hong, Haofei; Lin, Han; Li, Dan; Shi, Jie; Zhou, Zhifang; Wu, Zhimeng
Abstract : A β-Galactosidase-dependent glycoengineering strategy was developed for cancer cell surface glycan imaging and target immunotherapy in high selectivity and efficacy. Abstract : A β-Gal-dependent metabolic glycoengineering strategy was developed for tumor cell-selective surface glycan imaging with high efficacy. Combined with an antibody-recruiting strategy, targeted immunotherapy was achieved successfully based on this strategy.